2018
DOI: 10.3390/toxins10030108
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Specific Neutralization of Stx2a with a Camelid Single Domain Antibody Fragment

Abstract: Background: Shiga toxin-producing Escherichia coli (STEC) are a subset of pathogens leading to illnesses such as diarrhea, hemolytic uremic syndrome and even death. The Shiga toxins are the main virulence factors and divided in two groups: Stx1 and Stx2, of which the latter is more frequently associated with severe pathologies in humans. Results: An immune library of nanobodies (Nbs) was constructed after immunizing an alpaca with recombinant Shiga toxin-2a B subunit (rStx2aB), to retrieve multiple rStx2aB-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…This finding provides strong evidence for antigen-induced maturation of inter-Fab interactions for human antibodies, which may prove to be a common mechanism for increasing affinity against the PfCSP repeat region and for tandem repeat sequences in general. Recently, heavy-chain antibody fragments (nanobodies) derived from alpacas against a pentameric antigen were observed to have inter-nanobody contacts, suggesting that this mechanism may be present across certain antibodies in different species ( 31 ). A previous structure of antibody 2G12 to HIV Env revealed a novel domain swap within the Fabs of a single IgG molecule, where the heavy chain from one Fab paired with the light chain of the other Fab, such that a new V H -V H interface was formed that was also subject to somatic hypermutation ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…This finding provides strong evidence for antigen-induced maturation of inter-Fab interactions for human antibodies, which may prove to be a common mechanism for increasing affinity against the PfCSP repeat region and for tandem repeat sequences in general. Recently, heavy-chain antibody fragments (nanobodies) derived from alpacas against a pentameric antigen were observed to have inter-nanobody contacts, suggesting that this mechanism may be present across certain antibodies in different species ( 31 ). A previous structure of antibody 2G12 to HIV Env revealed a novel domain swap within the Fabs of a single IgG molecule, where the heavy chain from one Fab paired with the light chain of the other Fab, such that a new V H -V H interface was formed that was also subject to somatic hypermutation ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Camelid VHHs are a popular tool for constructing recombinant antibodies to detect and neutralize a range of targets [18,19,20,21,22,23,24]. In particular, it has been shown that HC-only antibodies or VHHs derived from HC-only antibodies, produced by camelids demonstrate strong anti-BoNT activities in animal models [6,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Clear advantages include the ability to recognize hidden antigenic sites that are inaccessible for conventional antibodies due to their structure; stability over a wide range of temperatures and pH; high solubility, as well as economical and facile expression and production in large quantities in microorganisms [15,17]. Several studies were conducted to test the potency of VHHs as inhibitors of viral infections [18] and different toxins, produced by such plants and microorganisms as Ricinus communis [19], Mycoplasma hominis [20], Clostridium tetani [21], Clostridium difficile [22], Crotalus durissus terrificus [23], and Shiga toxigenic Escherichia coli (STEC) [24]. It has been demonstrated that the antigen-binding region of VHHs produced by camelids showed strong anti-BoNT activities in animal models [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This finding provides strong evidence for antigen-induced maturation of inter-Fab interactions for human antibodies, which may prove to be a common mechanism for increasing affinity against the PfCSP repeat region and for tandem repeat sequences in general. Recently, heavy chain antibody fragments (nanobodies) derived from Alpacas against a pentameric antigen were observed to have inter-nanobody contacts, suggesting that this mechanism may be present across certain antibodies in different animal kingdoms (31). A previous structure of antibody 2G12 to HIV Env revealed a novel domain swap within the Fabs of a single IgG molecule, where the heavy chain from one Fab paired with the light chain of the other Fab, such that a new VH-VH interface was formed that was also subject to affinity maturation (32).…”
Section: Structural Ramifications and Implications For Vaccine Designmentioning
confidence: 99%